Faktor Kunci Keberhasilan Implementasi Blockchain dalam Identitas Berdaulat untuk Mendukung Target Pembangunan Berkelanjutan - Putra, Ega Pameza; Setiadi, Farisya (Prodi Sistem Informasi Universitas Dharma Andalas, 2025)
The development of information technology has entered an era of rapid digital transformation, where resource efficiency and data integration are key factors. Digital transformation, which not only affects the business industry but also the sustainable development sector, is driven by the emergence of the latest technologies such as artificial intelligence (AI) or artificial intelligence and distributed ledger technology (DLT) or distributed ledger technology or blockchain. Blockchain, with its decentralized and high security characteristics, offers great potential in various innovative applications, including in digital identity. Blockchain-based identity management systems have emerged as a solution to the problems of privacy, security, and control in digital identity management. In Indonesia, the launch of the Indonesia Digital Vision 2045 shows the government's commitment to encouraging the adoption of digital technology, including blockchain. This study aims to explore the potential of blockchain implementation in improving digital identity management as part of sustainable development efforts in Indonesia. The main focus of this study is on the key success factors needed for blockchain implementation in the context of digital identity in Indonesia, with the hope of contributing to further practice and study in this field.